ANALYSIS OF THE EFFECT OF PGPR FERTILIZER USE ON GROWTH ACCELERATION OF CHERRY TOMATO (Solanum lycopersicum var. cerasiforme) - Genade Kojongian; Orbanus Naharia; Helen Lawalata (Universitas Negeri Manado, 2022)
Cherry tomatoes are a type or commodity of horticulture that has a very relatively high economic value compared to ordinary tomatoes. Cherry tomato plants (Solanum lycopersicum var,. cerasiforme. It is one of the local plants that is neglected and not used and is often considered as a wild plant. This study aims to determine the effect of PGPR fertilizer application on the growth of cherry tomato plants. This research was carried out in the urban village). Rerewokan, West Tondano sub-district starting from August to November 2021. The method used is a quantitative method with the type of experimental research in the form of a Randomized Block Design (RAK) with five types of treatment, each repeated four times. P1 = without using fertilizer, P2 = 100ml, P3 = 200ml, P4 = 300ml, P5 = 400ml, so there were 20 treatment combinations, and the data obtained were then analyzed using analysis of variance (ANOVA). From the results of this study, it showed that good plant height growth was found in treatment P4 with the application of a mixture of PGPR fertilizer concentration of 300ml / 2 liters of water, because there was the most effective growth, while the growth in the number of leaves and the number of fruits was very good in treatment P2 with the addition of a mixture. PGPR fertilizer concentration 100ml / 2 liters of water.